2007
DOI: 10.1262/jrd.19076
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of Toll-Like Receptor mRNAs During Follicular Growth and in Response to Lipopolysaccharide in the Ovarian Follicles of Laying Hens

Abstract: Abstract. The aim of this study was to determine the changes in the mRNA expression of Toll-like receptors (TLRs) in hen ovarian follicles during follicular growth and in response to lipopolysaccharide (LPS). White follicles and the fifth largest to largest follicles (WF and F5-F1, respectively) were collected from laying hens. To examine the effects of LPS, the laying hens were treated intravenously with LPS (1 mg/kg BW) 0, 3, 6, 12 and 24 h before examination. Expressions of TLRs and IL-1β in the theca and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 42 publications
5
32
0
5
Order By: Relevance
“…Similar to the results obtained from F3 (third largest preovulatory follicle), granulosa layers extracted from hens treated intravenously with LPS (Subdei et al 2007), both TLR2 and TLR4 mRNA expressions were increased following treatment with LPS for 20 h, but not at the earlier time point of 4 h. The timing of up-regulation, however, differed for the largest (F1) preovulatory follicle, in which treatment with LPS elicited a significant increase in TLR2 and TLR4 mRNA levels after only 4 h. These data suggest a differential sensitivity to LPS-induced TLR mRNA based on stage of maturation, whereby an accelerated response is elicited in the follicle next to be ovulated.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar to the results obtained from F3 (third largest preovulatory follicle), granulosa layers extracted from hens treated intravenously with LPS (Subdei et al 2007), both TLR2 and TLR4 mRNA expressions were increased following treatment with LPS for 20 h, but not at the earlier time point of 4 h. The timing of up-regulation, however, differed for the largest (F1) preovulatory follicle, in which treatment with LPS elicited a significant increase in TLR2 and TLR4 mRNA levels after only 4 h. These data suggest a differential sensitivity to LPS-induced TLR mRNA based on stage of maturation, whereby an accelerated response is elicited in the follicle next to be ovulated.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with a recent report in which i.v. LPS increased ILIB mRNA in granulosa layers from hen preovulatory follicles (Subdei et al 2007). While ILIB was the only cytokine found to be transcriptionally regulated following stimulation with LPS in either study, these data do not preclude additional mediators of LPS-induced cell death.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Therefore, we developed an in vitro model to investigate the timing of response to LPS on patterns of gene expression in rooster SCs. In hens, it has been reported that the oviduct, as well as ovarian follicular and stromal cells, expresses TLRs, AvBDs, as well as proinflammatory cytokines and chemokines, and the expression of these molecules was upregulated by LPS stimulation (Subedi et al 2007, Abdel Mageed et al 2008, Ozoe et al 2009, Woods et al 2009, Abdelsalam et al 2011, Nii et al 2011. Similar to the female reproductive tract, the gene expression data presented in this study revealed that rooster SCs responded to LPS stimulation.…”
Section: Discussionsupporting
confidence: 59%